A Systematic Literature Review of Entrepreneurial Human Capital and Employee Performance in Public Organizations - Albertus Yudha Poerwadi; Yunia Wardi; Susi Evanita; Hendrik Heri Sandi (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2026)
Public sector organizations, including healthcare institutions, are under increasing pressure to enhance employee performance amid digital transformation, service complexity, and rising public expectations. Entrepreneurial Human Capital (EHC), reflected in innovation capability, proactiveness, adaptability, and opportunity recognition, has emerged as a critical resource for improving organizational effectiveness. This study synthesizes empirical evidence on the role of EHC in improving employee performance in public organizations. A systematic literature review was conducted following the PRISMA framework. Articles were retrieved from PubMed, Scopus, EBSCOhost, and Google Scholar. Thirty-one eligible studies were included in the final synthesis. The findings indicate that EHC enhances employee performance by strengthening initiative, adaptive decision-making, innovation, and problem-solving capacity. Innovative work behavior, knowledge sharing, and organizational learning were identified as key mediating mechanisms, whereas leadership support, organizational climate, and digital capability functioned as important moderating factors. These findings suggest that public organizations should prioritize capability-development strategies that foster innovation and adaptive behavior rather than relying solely on formal qualifications. Strengthening EHC may support sustainable employee performance and more responsive public service delivery, including in healthcare institutions.